1996
DOI: 10.1007/bf02087913
|View full text |Cite
|
Sign up to set email alerts
|

Small volume isosmotic polyethylene glycol electrolyte balanced solution (PMF-100) in treatment of chronic nonorganic constipation

Abstract: The present multicenter double-blind placebo-controlled trial evaluates the therapeutic effectiveness of small-volume daily doses of an isosmotic polyethylene glycol (PEG) electrolyte solution in the treatment of chronic nonorganic constipation. After a complete diagnostic investigation, patients still constipated at the end of a four-week placebo-treatment run-in period were enrolled and randomized to receive either placebo or PEG solution 250 ml twice a day for the following eight weeks. Patients were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 12 publications
2
74
0
5
Order By: Relevance
“…Acceleration of CTT with ROM was associated with improvement in bowel symptoms in constipated patients in several clinical trials that evaluated polyethylene glycol, 80 tegaserod, 81 and prucalopride.…”
mentioning
confidence: 97%
“…Acceleration of CTT with ROM was associated with improvement in bowel symptoms in constipated patients in several clinical trials that evaluated polyethylene glycol, 80 tegaserod, 81 and prucalopride.…”
mentioning
confidence: 97%
“…Numerous trials have shown both electrolyte-enriched PEG and electrolyte-free PEG to be effective in patients with chronic constipation. 115,[118][119][120][121][122][123][124][125][126][127] A meta-analysis concluded that PEG treatment resulted in a highly significant increase in defecations per week over placebo. 128 In particular, a meta-analysis involving 10 RCTs found that PEG was better than lactulose with respect to the outcomes of stool frequency per week, form of stool, relief of abdominal pain, and the need for additional products.…”
mentioning
confidence: 99%
“…2 Laxatives with an osmotic eVect appear to be consistently associated with significant improvements in frequency, consistency, straining, and pain compared with placebo based on the results of two systematic reviews 2 3 and additional small trials. [47][48][49][50] There is little evidence for diVerences in eVectiveness between osmotic laxatives and other treatments. Two small hospital based RCTs compared polyethylene glycol (PEG) 3350 with lactulose 51 and ispaghula (Konsyl), 52 respectively.…”
Section: Effectiveness Of Laxative Treatmentsmentioning
confidence: 99%